4(x-3)=-8(x+1)

Simple and best practice solution for 4(x-3)=-8(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)=-8(x+1) equation:


Simplifying
4(x + -3) = -8(x + 1)

Reorder the terms:
4(-3 + x) = -8(x + 1)
(-3 * 4 + x * 4) = -8(x + 1)
(-12 + 4x) = -8(x + 1)

Reorder the terms:
-12 + 4x = -8(1 + x)
-12 + 4x = (1 * -8 + x * -8)
-12 + 4x = (-8 + -8x)

Solving
-12 + 4x = -8 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-12 + 4x + 8x = -8 + -8x + 8x

Combine like terms: 4x + 8x = 12x
-12 + 12x = -8 + -8x + 8x

Combine like terms: -8x + 8x = 0
-12 + 12x = -8 + 0
-12 + 12x = -8

Add '12' to each side of the equation.
-12 + 12 + 12x = -8 + 12

Combine like terms: -12 + 12 = 0
0 + 12x = -8 + 12
12x = -8 + 12

Combine like terms: -8 + 12 = 4
12x = 4

Divide each side by '12'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| s/13=4 | | [-1,2],y=1/2x-3 | | 45+x=x | | -19=6w+4w | | -19-1m=8(1+1m) | | -2(3a+5)=-46 | | -5(3u-4)+6u=3(u+8) | | 9/7=z/2 | | 10-x+7=20 | | 3/14(6/13) | | 7-8=13 | | 9x^2-8x+1=-x^2-2 | | 7(y+4.5)= | | -2.3v=6/5 | | x/2-2/5=3/2 | | 7-3x=-29 | | 6+49x=21+42 | | x/2-2/5=2/3 | | 88/-4 | | 11/22x-7/15=-2 | | 8/20(5/19) | | f(x)=2x^3-4x+2 | | (1+4r)(6)= | | 0=ln(cos(x)) | | 6p-5=113 | | 26=2(2x-4)+6 | | 7x+7=35+3x | | 8z-3=10z-7 | | 6/8x=6/8 | | 2x+8=5x+8 | | z-6.9=-5.4 | | 20=17+x-10 |

Equations solver categories